PENGARUH KOMPETENSI APARATUR, KOMITMEN ORGANISASI, PARTISIPASI MASYARAKAT, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Empiris pada 3 Kecamatan yaitu Kecamatan Tandun, Rokan IV Koto, dan Pagaran Tapah Darussalam Kabupaten Rokan Hulu Tahun 2019) - Popi, Pera; Yusralain, Yusralain; Adhitya, Putra Agri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to examine the effect of apparatus competence, organizational commitment, community participation, and internal control systems on the accountability of village fund management. The population in this study were all village officials in 25 villages in Tandun, Rokan IV Koto and Pagarantapah Darussalam Districts in Rokan Hulu Regency. The sample in this study were village government officials who implemented village fund management, with the criteria of the Village Head, Village Secretary, Village Treasurer, General Head and BPD, with a total sample of 125 respondents choosed by using the purposive sampling method. This study uses primary data by distributing questionnaires. The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that apparatus competence, organizational commitment, community participation and internal control systems affect the accountability of village fund management.Keywords: Apparatus Competence, Organizational Commitment, Community Participation, Internal Control Systems and Accountability of Village Fund Management.